Practical remediation of 3-nitro-1,2,4-triazol-5-one wastewater - Chew, Siao Chien; Tennant, Mat; Mai, Nathalie; McAteer, Daniel; Pons, Jean-François (Wiley, 2017)
Limiting environmental impact is a top priority for the chemical industry, and manufacturing practices need to be well controlled to avoid any potential contamination. In order to reduce waste streams during the processing of 3-nitro-1,2,4-triazol-5-one (NTO), potentially evironmental hazardous at concentrations of 1 g/l, we investigated the potential remediation and recycling of water using a wide range of commercial sorption media. We studied the effect of experimental conditions, including flow rate, initial contaminant concentration and temperature. This led to the selection of Amberlyst A26 OH in a batch process and Activated Carbon in continuous flow, as the most effective sorption methods. Using high performance liquid chromatography photodiode array detection (HPLC-PDA), NTO was quantified from solutions, before and after remediation, showing a complete removal from a 10 g/l NTO solution. Our purification method therefore appears to be suitable for the remediation of NTO-contaminated wastewater.